Mobile learning: teaching and learning with mobile phone and Podcasts. - Moura, Adelina (2008)
Mobile learning, a natural extension of distance education, supported by wireless mobile technologies is an emerging pedagogical learning model which requires new forms of teaching and learning. Being aware of the importance of this standard, we held a series of educational experiments utilizing mobile devices such as mobile phones and MP3/MP4 players to evaluate the implications of mobile technologies in individual and collaborative learning. The preference for these technologies is the fact that they are in the students’ hands and have a great potential in the education system. Among the experiments we highlighted the hearing of Podcasts on curriculum content. In this paper we present data about the students’ positive perceptions of Podcasts regarding their usefulness and educational value. These allow us to draw conclusions about the educational potential of these tools.